The translation of Salazar’s speeches into English: a case study on soft power practices in 20th century Portugal - Chumbo, Isabel (2022)
The concept of soft power is visible in many forms. According to Nye (2004), the use of rhetoric is the resource found at the basis of soft power, and this idea is reinforced by Rothmann, for whom “strategically utilizing rhetoric or creating new rhetoric and symbols of a particular discourse allows actors to influence world politics through soft power” (Rothmann 2011, 60). This means that a specific kind of narrative can constitute an example of soft power practice in a given setting. Hence, this paper will focus on the context of the 20th century Estado Novo dictatorship in the period from 1933 to the aftermath of the second World War in Portugal. This regime employed soft power practices through the systematic publication of political texts, more concretely of the speeches written and delivered by dictator Oliveira Salazar. A state entity called National Propaganda Secretariat was the commissioner of most of these texts and in some cases the initiator of the translations of these speeches into several languages and published in different countries. This work will provide insight into the case of the translation of Salazar’s speeches into English as a means to influence international relations with a specific target audience in mind. This was carried out through the qualitative analysis of translation shifts occurred in a bilingual corpus of 29 speeches. This corpus will also contribute towards the understanding of the translation process carried out by the English translator of the work Doctrine and Action (1939), published by Faber and Faber in the UK. The translation of the speeches by Salazar can be viewed as a case study in the wider scope which is translation during the Estado Novo in Portugal, especially considering the innovative approach of translation into a foreign tongue and the underlying awareness of the country’s soft power needs in the European context. This unspoken and unwritten policy is visible in practice. The analysis performed during a wider study reached results which suggest that these soft power practices were not only deliberate but also viewed as essential in the regime’s ongoing political behaviour.